2019
DOI: 10.1101/2019.12.18.881540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rise of diversity in metabolic platforms across the Candidate Phyla Radiation

Abstract: A unifying feature of the bacterial Candidate Phyla Radiation (CPR) is a limited and highly variable repertoire of biosynthetic capabilities. However, the distribution of metabolic traits across the CPR and the evolutionary processes underlying them are incompletely resolved. Here, we selected~1,000 genomes of CPR bacteria from diverse environments to construct a robust internal phylogeny that was consistent across two unlinked marker sets. Mapping of glycolysis, the pentose phosphate pathway, and pyruvate met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…The sparse and scattered distribution of the putative ETC gene homologs in Patescibacteria and DPANN ( Figure 8 ) suggest HGT origins rather than ancestral inheritance. This is consistent with the phylogenetic reconstructions of other energy transducing genes identified in Patescibacteria, which also suggest evolutionary origins from HGT ( Jaffe et al, 2020 ). Collectively, our observations indicate that the absence of complete electron transport chains in Patescibacteria and DPANN is an ancestral feature of the two superphyla, which we propose is more parsimonious than multiple gene loss events due to obligate symbiosis ( Brown et al, 2015 ; Hug et al, 2016 ; Castelle et al, 2018 ; Dombrowski et al, 2019 ; Méheust et al, 2019 ).…”
Section: Resultssupporting
confidence: 88%
“…The sparse and scattered distribution of the putative ETC gene homologs in Patescibacteria and DPANN ( Figure 8 ) suggest HGT origins rather than ancestral inheritance. This is consistent with the phylogenetic reconstructions of other energy transducing genes identified in Patescibacteria, which also suggest evolutionary origins from HGT ( Jaffe et al, 2020 ). Collectively, our observations indicate that the absence of complete electron transport chains in Patescibacteria and DPANN is an ancestral feature of the two superphyla, which we propose is more parsimonious than multiple gene loss events due to obligate symbiosis ( Brown et al, 2015 ; Hug et al, 2016 ; Castelle et al, 2018 ; Dombrowski et al, 2019 ; Méheust et al, 2019 ).…”
Section: Resultssupporting
confidence: 88%
“…Given the unique challenges of the soil environment for microbes, we next assessed whether these soil CPR and DPANN exhibited similar traits to their counterparts in other environments. Recent studies show that CPR bacteria generally appear to have the capacity for glycolysis and fermentation (17), but often lack complete pathways to predictably de novo synthesize nucleotides and have many gaps in metabolism that suggest an obligate symbiotic lifestyle (8). We find that most of the genomes from this sampling effort encode the three central glycolysis enzymes reportedly found in nearly all CPR bacteria: triose phosphate isomerase (TIM), glyceraldehyde 3-phosphate (GAPDH), and phosphoglycerate kinase (PGK) (17).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies show that CPR bacteria generally appear to have the capacity for glycolysis and fermentation (17), but often lack complete pathways to predictably de novo synthesize nucleotides and have many gaps in metabolism that suggest an obligate symbiotic lifestyle (8). We find that most of the genomes from this sampling effort encode the three central glycolysis enzymes reportedly found in nearly all CPR bacteria: triose phosphate isomerase (TIM), glyceraldehyde 3-phosphate (GAPDH), and phosphoglycerate kinase (PGK) (17). As expected, based on prior studies of CPR bacteria and DPANN archaea (8), the genomes contain few if any TCA cycle genes and lack genes of the electron transport chain, and for synthesis of lipids and nucleotides (Fig 1d), suggesting they live anaerobic lifestyles with strong dependence on resources from other organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Genomes containing genes clustering with the cytb5MY sequences were selected for further analysis, and annotated using InterProScan v5.48-83.0 (Jones et al, 2014). Taxonomic identification of these genomes was performed against the dereplicated genomes provided by Jaffe et al (2020) using fastANI (Jain et al, 2018) with default parameters or, if no results were found, by using a fragment length threshold of 1000 bp. Gene synteny analyses were performed using the genoPlotR package (Guy et al, 2010) and the Gene Neighborhood Viewer and Chromosomal Cassette Viewer tools (Mavromatis et al, 2009) of the Integrated Microbial Genomes (IMG) database (Chen et al, 2019).…”
Section: Gene Cluster Analysesmentioning
confidence: 99%